A Puzzle About Parsimony - Peter Finocchiaro (Dialectica, 2022)
In this paper, I argue for the instability of an increasingly popular position about how metaphysicians ought to regard parsimony. This instability is rooted in an unrecognized tension between two claims. First, we as metaphysicians ought to minimize the number of ontological kinds we posit. Second, it is not the case that we ought to minimize the number of ideological expressions we employ, especially when those expressions are of the same ideological kind (e.g. the compositional predicates "is a part of" and "overlaps"). I argue that the two claims are in tension with one other. At the very least, minimizing the number of ontological kinds posited entails minimizing the number of expressions employed---more specifically, the "ontologically committing" predicates. But, plausibly, the tension runs deeper than that. I suggest that minimizing the number of ontological kinds just is a specific way of minimizing the number of ideological expressions employed in stating a theory. The two activities target the same aspect of reality, the world's metaphysical structure. I end by evaluating three different responses to this puzzle. Ultimately, I suggest that metaphysicians should treat the minimization of the number of ideological expressions as more important than it currently is treated.